From economic gains to social losses: How stories shape expectations in the case of German municipal finance - Florian Fastenrath; Agnes Orban; Christine Trampusch (Max Planck Institute for the Study of Societies, 2017)
This paper analyzes how stories shaped treasurers' expectations in municipal swap activities and contributes to the sociological debate on the mechanisms of expectation formation. Employing a deductive variant of process tracing, it synthesizes the literature on expectations in economic decision making with the literature on the diffusion of "ideas", "myths", and "fashions" in organization theory and management studies. The swap story has spread since the mid-1990s among German municipalities. At the heart of this story is the replacement of traditional borrowing with active portfolio optimization; financial instruments known as swaps play a leading role. This paper examines how stories shape expectations. Specifically, it delves into how the swap story, as a solution to the financial woes of local governments, shaped these governments' expectations despite the uncertainty resulting from the instruments' complexity. We argue that the effect of stories on expectations depends on timing. Expectations at an early stage are shaped by economic analyses to reduce uncertainty, while expectations at a later stage are primarily shaped by societal pressures and an established trend. These two distinct mechanisms produce expectations related to economic and social consequences, respectively. Selecting four typical cases, our analysis confirms that stories affected the formation of treasurers' expectations regarding the use of swaps through these different mechanisms. – – Dieses Papier analysiert, wie Stories die Erwartungen von Stadtkämmerern bei dem Abschluss von Swapgeschäften geprägt haben, und trägt somit zur soziologischen Debatte über die kausalen Mechanismen der Erwartungsbildung bei. Unter Verwendung einer deduktiven Variante der Prozessanalyse wird die Literatur zu Erwartungen bei ökonomischer Entscheidungsfindung mit den Konzepten der Diffusion von "Ideen", "Mythen" und "Fashions" aus der Organisationstheorie und Betriebswirtschaft zusammengeführt. Die Swap-Story verbreitete sich seit Mitte der 1990er-Jahre unter deutschen Kommunen. Im Zentrum steht dabei das Ersetzen eines traditionellen passiven Umgangs mit Schulden durch ein aktives Portfoliomanagement, bei dem die als Swaps bekannten Finanzinstrumente eine entscheidende Rolle einnehmen. Diese Studie geht der Frage nach, wie die Erwartungen der Kommunen durch die Swap-Story als Lösung ihrer fiskalischen Probleme beeinflusst wurden, obwohl die Instrumente mit extremer Ungewissheit behaftet sind. Wir argumentieren, dass der Effekt von Stories auf Erwartungen von der zeitlichen Dimension abhängt. Während Erwartungen in einer frühen Phase der Einführung von ökonomischen Analysen geprägt sind, um Unsicherheit zu reduzieren, so sind sie in einer späteren Phase primär von gesellschaftlichem Druck und einem bereits etablierten Trend beeinflusst. Diese zwei verschiedenen Mechanismen erzeugen Erwartungen, die jeweils ökonomischen sowie sozialen Konsequenzen zugehörig sind. Unsere Analyse verifiziert anhand vier ausgewählter typischer Fälle, dass Stories die Erwartungsbildung von Kämmerern hinsichtlich der Nutzung von Swaps durch diese verschiedenen Mechanismen beeinflussen.
hdl:11858/00-001M-0000-002E-8632-D
Keywords: 300; stories; expectations; financial innovations; economic sociology; financialization; causal mechanisms; Erwartungen; Finanzinnovationen; Wirtschaftssoziologie; Finanzialisierung; kausale Mechanismen